Learning Styles: Tools for Understanding Media Selection and Learners’ Academic Achievement in Physics - Folashade Afolabi (Journal of Educational Sciences, 2021)
The study examined learners’ learning styles and media format on academic achievement among physics distance learners. Two hundred and Ninety-five learners were used for the study and were selected through purposive sampling techniques by balloting. Fleming NARK model Index of Learning Style questionnaire (ILSQ) and PAT Physics Achievement Test with reliability coefficient of 0.88 and 0.78 using test-retest method and KR-21. The two instruments were used for data collection. Data collected were analyzed using Analysis of Covariance (ANCOVA). The results showed that no significant difference exists in the achievement of learners with varied learning styles (visual, auditory and kinesthetic) when taught using print format, audio and audio visual. However, results indicated that Kinesthetic is the most effective learning style when learners were taught with audiovisual media format which significantly influences learners’ achievement. The study recommends that there is need for teachers to diversify their strategy to compliments all types of learners.